2010
DOI: 10.1111/j.1365-3156.2009.02443.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of compliance with a mass drug administration programme for lymphatic filariasis in Orissa State, India 2008

Abstract: Summaryobjectives To assess the performance of an educational campaign to increase adherence to a massadministered DEC regimen against lymphatic filariasis (LF) in Orissa, and to identify factors that could enhance future campaigns.method Randomized cluster survey, comparing areas that did and did not receive the educational campaign, using a household coverage survey and knowledge, attitudes and practices (KAP) survey.results LF MDA coverage for the entire population (n = 3449) was 56% (95% CI: 50.0-61.9). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 18 publications
2
39
0
Order By: Relevance
“…Residents of one area received the standard pre-MDA education that is typical for Orissa (MDA-only). Another area had enhanced community-based pre-MDA education that was designed to address barriers to compliance identified in the 2007 MDA (Com-MDA) [13]. In the third area, which also received enhanced community-based pre-MDA education, a lymphedema management program had been initiated earlier in the year (Com-MDA+LM).…”
Section: Resultsmentioning
confidence: 99%
“…Residents of one area received the standard pre-MDA education that is typical for Orissa (MDA-only). Another area had enhanced community-based pre-MDA education that was designed to address barriers to compliance identified in the 2007 MDA (Com-MDA) [13]. In the third area, which also received enhanced community-based pre-MDA education, a lymphedema management program had been initiated earlier in the year (Com-MDA+LM).…”
Section: Resultsmentioning
confidence: 99%
“…For example, a KAP study in Thailand showed the positive influence of increasing community knowledge on controlling and preventing dengue, thereby improving prevention practices (Koenraadt et al 2006). What’s more, some other surveys adopted KAP model include identifying knowledge gaps, cultural beliefs, and behavioral patterns that may pose barriers to controlling infectious diseases (Krentel et al 2006; Matibag et al 2007), design of relevant public health awareness campaigns (Cantey et al 2010), establishing baseline data for planning and implementation, and evaluating control program.…”
Section: Discussionmentioning
confidence: 99%
“…CASA partnered with the Centers for Disease Control and Prevention (CDC) to evaluate the effectiveness of their program. This evaluation found that adherence to the DEC regimen was less than 60% and failed to detect a significant impact of the community-based education campaign [16]. However, it identified barriers to and predictors of adherence.…”
Section: Introductionmentioning
confidence: 89%